A Tablet-Based Documentation Tool for In-Hospital Resuscitations. (September 2015) - Reinhardt, D.; Kraft, A-K.; Albert, M.; Grundgeiger, T.; Happel, O.; Steinisch, A.; Wurmb, T.
The exact documentation of cardiopulmonary resuscitations—in particular the exact time of intervention delivery—is important for checking and improving quality. However, due to time-critical, stressful treatment and mostly retrospective documentation, data quality is often poor. This paper describes the development of a tablet-based application for documentation of in-hospital cardiopulmonary resuscitations that enables real-time documentation by a member of the resuscitation team. The application was developed following a comprehensive user-centered design process. Due to an efficient context-related information architecture, the application has the potential to enable real-time documentation of certain interventions and to accelerate time-consuming documentation after the resuscitation ended. Furthermore, the use of the application may contribute to the optimization of resuscitation processes and resuscitation training by providing more accurate and reliable data.